Kemampuan Pemecahan Masalah dalam Pemodelan Matematika: Systematic Literature Review (SRL) (Asimtot : Jurnal Kependidikan Matematika, 2026)
Abstract: Problem solving is the core of mathematics education because the process of formulating and solving problems greatly determines the quality of students’ mathematical reasoning. Mathematical modeling serves as a bridge between abstract concepts and real-world phenomena, as emphasized through various educational studies and international assessments. This study aims to describe research developments, identify the characteristics of problem solving, and reveal gaps and recommendations in the context of mathematical modeling. The method used is a Systematic Literature Review (SLR) with data sources from Scopus-indexed articles from 2020–2025 using the keywords “mathematical modeling” and “problem solving.” The selection process produced 19 relevant articles that were analyzed using bibliometric techniques and visual mapping through VOSviewer. The results show that publications related to mathematical modeling experienced fluctuations, with a tendency to decline since 2022. The reviewed studies reveal two major focuses: the application of modeling to solve complex problems in science, engineering, and optimization, and its use in pedagogical development, particularly in improving problem-solving abilities and mathematical literacy. The analysis also highlights gaps related to methodological limitations and challenges faced by educators in integrating modeling effectively
Keywords: Mathematic Education; Mathematical Modeling; Problem Solving; Systematic Literature Review